Immunosuppression of Tumor-Derived Factors Modulated Neutrophils in Upper Tract Urothelial Carcinoma Through Upregulation of Arginase-1 via ApoA1-STAT3 Axis - Chih-Chia Chang; Chia-Bin Chang; Cheng-Huang Shen; Ming-Yang Lee; Yeong-Chin Jou; Chun-Liang Tung; Wei-Hong Lai; Chi-Feng Hung; Meilin Wang; Ya-Yan Lai; Pi-Che Chen; Shu-Fen Wu (Cells)
Upper tract urothelial carcinoma (UTUC) presents aggressive features and a tumor microenvironment with T cell depletion. However, the role of tumor-associated neutrophils in UTUC remains unclear. This study aimed to investigate how UTUC tumor-derived factors modulate neutrophils and their impact on T cell immune responses. Our findings demonstrate that UTUC secreted tumor-derived factors, with apolipoprotein A1 (Apo-A1) being the predominant factor, which upregulated arginase-1 expression in neutrophils. STAT3 activation was responsible for the upregulation of arginase-1 in neutrophils. Blocking the interactions between Apo-A1 and its receptors reduced arginase-1 expression in neutrophils treated with tumor tissue culture supernatant (TTCS). Moreover, both CD4+ T and CD8+ T cell proliferation were inhibited by neutrophils treated with Apo-A1 or TTCS. Importantly, blocking Apo-A1 signaling in neutrophils reversed the inhibitory effects on T cells. In UTUC patients, the neutrophil-to-lymphocyte ratio was higher than that in healthy subjects. The expression of arginase-1 in neutrophils and the level of Apo-A1 within UTUC tumors were negatively correlated with tumor-infiltrating CD4+ T cells. Additionally, neutrophils from UTUC patients showed increased expression of arginase-1 and exhibited inhibitory effects of T cell functions. These findings suggest that UTUC orchestrates an immune-suppressive microenvironment through Apo-A1-mediated upregulation of arginase-1 in neutrophils, ultimately leading to the inhibition of T cell proliferation.